Fish and wave ebook - Ruzzier, Sergio (I Can Read Comics, Level 1., 2022)
Let's read comics! I Can Read Comics is an early reader line that familiarizes children with the world of graphic novel storytelling and encourages visual literacy in emerging readers. When a tiny wave grows bigger and bigger, what's a fish to do? Fish and Wave by Sergio Ruzzier is a playful exploration of what it really means to go with the flow. Fish and Wave is a Level One I Can Read Comic, a simple story for shared reading. Praise for Fish and Sun Publishers Weekly Best Book of 2021 Kirkus Best Book of 2021 Junior Library Guild Selection 4 Starred reviews from Publishers Weekly, Kirkus Reviews, School Library Journal, The Horn Book